Understanding the Impact of Socioeconomic Factors on Early Childhood Development in Marginalised Roma Communities: The Role of Parental Education and Household Equipment - Plavnicka, Jana; Chovan, Shoshana; Filakovska Bobakova, Daniela (Children, 2024)
This study aimed to explore the effect of socioeconomic disadvantage accumulated in marginalised Roma communities (MRCs) on early childhood development and to assess the role of selected socioeconomic indicators in the association between belonging to MRCs vs. the majority and early childhood development. We obtained cross-sectional data from 232 mother-child dyads from MRCs and the majority population. The differences in early childhood development and background variables between the two groups were tested using chi-square and Mann-Whitney U tests. The moderated mediation was tested using PROCESS Macro in SPSS Model 14 on 5000 bootstrap samples. Statistically significant differences between children from MRCs and the majority were found in terms of maternal age, parental education, household equipment, as well as early childhood development. Household equipment moderated the indirect effect of being from MRCs vs. the majority on early childhood development through parental education. The indirect effect through parental education was high at a low household equipment level, reduced at an average level and non-significant at a high level of household equipment. Our study uncovered disparities in early childhood development between children from MRCs and the majority population. Parental education significantly influenced developmental outcomes, while household equipment mitigated its impact.